IMPROVEMENT OF STUDENT LEARNING OUTCOMES USING THE PROBLEM-BASED LEARNING MODEL ASSISTED BY CANVA ON ENVIRONMENTAL CHANGE MATERIAL - Annisa, Nur; Ningsih, Kurnia; Yuniarti, Anisyah; Titin, Titin; Wahyuni, Eko Sri (Universitas Tanjungpura, 2025)
The learning outcomes obtained by students have been low due to the implementation of the learning implementation process that has not been maximized. The purpose of this study was carried out to determine the implementation of the learning process and student learning outcomes using the PBL model assisted by Canva. The research method used is classroom action research conducted with 2 cycles and each cycle consists of 2 meetings. The stages of this research consist of planning, implementation, observation, and reflection. The instruments used are observation sheets of the learning implementation process to determine the achievement of learning objectives and learning outcomes test sheets to measure students' mastery of the material provided. Data collection techniques are observation, learning outcome tests, and documentation. Before being used, all instruments were validated first by validators and continued with reliability measurements. The results of this study are the process of implementing learning using the PBL model assisted by Canva increased with a cycle I completeness percentage of 91.32% to 93.87%. This increase affected the learning outcomes of students with a percentage of completeness in cycle I of 81.66% and cycle II of 90%. This study proves that the use of PBL models assisted by canva can improve the learning implementation process and student learning outcomes.